Influence of a Magnetic Field on the Structure, Morphology and Gas Sensing Characteristics of ZnO: Al Thin Films Prepared by Pulsed Laser Ablation - Abbas, Zahraa Marid; Abbas, Qusay Adnan (Iraqi Journal of Science, 2024)
In this work, aluminium-doped zinc oxide (AZO) nanostructure at 0.3 wt% and 0.5 wt% Al was synthesized using the pulse-laser ablation technique in liquid(PLAL) using pulsed Nd: YAG laser of a fundamental wavelength of (1064 nm). The process was done in the absence and presence of an external magnetic field. The deposited AZO nanostructures by drop-casting on etched-Si wafers were examined by different techniques. The XRD test illustrates enhancing the crystallinity of the prepared thin films by applying an external magnetic field. The FESEM images displayed the change of nanostructure to nano-sheets of high surface area after using a 77.2 mT permanent magnet placed behind the target during the ablation process. The gas sensor based on the AZO nanostructures has higher sensitivity against NO2 than H2S. Increasing the Al ratio from 0.3 wt% to 0.5 wt% changed the properties of the prepared samples to have small porosity and small surface area, which negatively affected the properties of the sensor